Stereoselective quenching of cedryl carbocation in epicedrol biosynthesis - Shinde, Sandip S.; Navale, Govinda R.; Said, Madhukar S.; Thulasiram, Hirekodathakallu V. (Tetrahedron Letters, 2016)
Epicedrol synthase catalyzes the cyclization of achiral diphosphate substrate, (E,E)-farnesyldiphosphate (FPP) into epicedrol. GC-MS analysis of assay extracts obtained by incubating FPP with epicedrol synthase in 21.6 at % H2(18)O buffer showed the molecular ion of 224 for epicedrol. The labeled oxygen study presented here unambiguously demonstrates that the hydroxyl group of the epicedrol synthase enzymatic product, epicedrol, is derived from a water molecule, not from the phosphate moiety of the FPP. (C) 2016 Elsevier Ltd. All rights reserved.

Synthesis, biological evaluation and molecular docking of novel coumarin incorporated triazoles as antitubercular, antioxidant and antimicrobial agents - Shaikh, Mubarak H.; Subhedar, Dnyaneshwar D.; Shingate, Bapurao B.; Khan, Firoz A. Kalam; Sangshetti, Jaiprakash N.; Khedkar, Vijay M.; Nawale, Laxman; Sarkar, Dhiman; Navale, Govinda R.; Shinde, Sandip S. (Medicinal Chemistry Research, 2016)
A series of new coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular activity in vitro against Mycobacterium tuberculosis H37Ra, antioxidant activity by DPPH radical scavenging assay, antimicrobial activity in vitro against three gram-positive bacteria (Staphylococcus aureus, Micrococcus luteus and Bacillus cereus) and three gram-negative bacteria (Escherichia coli, Pseudomonas fluorescens and Flavobacterium devorans as well as three fungi (Aspergillus niger, Penicillium chrysogenum and Curvularia lunata). The bioactive assay showed that some synthesized coumarin triazoles displayed comparable or even better antitubercular, antioxidant, antibacterial and antifungal efficacy in comparison with reference drugs. Furthermore, docking study has been performed against DprE1 enzyme of M. tuberculosis that showed good binding interactions. Moreover, the synthesized compounds were also analyzed for ADME properties and showed potential to build up as good oral drug candidates. New coumarin-based 1,2,3-triazole derivatives were designed, synthesized and evaluated for their antitubercular, antioxidant, antibacterial and antifungal activity. Some of the coumarin-based triazole derivatives displayed comparable or even better efficacy in comparison with reference drugs. Molecular docking study has been performed against DprE1 enzyme of Mycobacterium tuberculosis showed good binding interactions. [GRAPHICS] .
Keywords: 1; 2; 3-Triazole; ADME prediction; Antimicrobial; Antioxidant; Antitubercular; Click chemistry; Docking study

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2019)
A sesquiterpene epicedrol cyclase mechanism was elucidated based on the gas chromatography coupled to electron impact mass spectrometry fragmentation data of deuterated (H-2) epicedrol analogues. The chemo-enzymatic method was applied for the specific synthesis of 8-position labelled farnesyl pyrophosphate and epicedrol. EI-MS fragmentation ions compared with non-labelled and isotopic mass shift fragments suggest that the H-2 of C6 migrates to the C7 position during the cyclization mechanism.

Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis (Retraction of Vol 9, Pg 28258, 2019) - Said, Madhukar S.; Navale, Govinda R.; Gajbhiye, Jayant M.; Shinde, Sandip S. (RSC Advances, 2020)
Retraction of `Synthesis of deuterated isopentyl pyrophosphates for chemo-enzymatic labelling methods: GC-EI-MS based 1,2-hydride shift in epicedrol biosynthesis' by Madhukar S. Said et al., RSC Adv., 2019, 9, 28258-28261.

Size does matter: antibacterial activities and cytotoxic evaluation of polymorphic CuO nanostructures - Desai, Dnyanada G.; Navale, Govinda R.; Late, Dattatray J.; Dharne, Mahesh S.; Walke, Pravin S. (Journal of Materials Science, 2023)
Nanostructured materials play a significant role in antibacterial activities. However, understanding the geometrical influence at the nanoscale in terms of size- and shape-correlated physical properties on antibacterial activities is very essential. Herein, we report the antibacterial influence of various copper oxide nanostructures (CuO NS) such as nanoparticles (NPs) (< 10 nm), nanospheres (NSs) (50-100 nm), and porous nanoflowers (NFs) (asymptotic to 350 nm). The XRD confirmed the crystalline nature of CuO NPs without impurities. The antibacterial activities of CuO NPs were investigated by the microplate dilution method and confocal laser scanning microscopic (CLSM) imaging. NPs having a diameter less than 10 nm exhibited significant damage to the bacterial cell membrane than NSs and NFs. Interestingly, NPs illustrated relatively low antibacterial activity against Gram-negative bacteria (Pseudomonas aeruginosa and Acinetobacter baumannii) than Gram-positive bacteria (Staphylococcus aureus and Staphylococcus epidermidis). Acinetobacter baumannii was found to be more susceptible to the NPs than other bacterial strains, attributed to its increased membrane permeability. The death phase was observed at a concentration of 15.6 mu g mL(-1) and 3.9 mu g mL(-1) for P. aeruginosa and A. baumannii, respectively, when treated with CuO NP after the 8 h of incubation. Similarly, for S. aureus and S. epidermidis, the death phase was observed at the concentration of 31.2 mu g mL(-1) and 250 mu g mL(-1), respectively. Furthermore, as the cell cytotoxicity measurements against human fibroblast L9239 cells revealed that CuO NPs were safe. The morphological and cell viability assay demonstrated 100% cell survival, when treated with NPs and NSs (5, 10, and 25 mu g mL(-1)), signifies no cytotoxicity. Therefore, CuO nanoparticles can be used for clinical and therapeutic applications.